Analisis Hukum Islam Terhadap Jual Beli Online - Dyana Dwi Indira; Futri Amalia Zahara; Hendy Cahya Wiguna; Hikmatul Aulia; Wise Cahyati Sholihat; Yayat Suharyat (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The purpose of this study was to investigate the Islamic legal view of online buying and selling by considering the principles of sharia concerned. Online buying and selling has become a common occurrence in the ever-evolving digital world. Online transactions for buying and selling are commonplace now and present a number of issues and problems in relation to Islamic law. An examination of Islamic law on online buying and selling is essential in this situation to understand the application and consequences of Shariah. The research technique used is a qualitative descriptive approach, which requires to read primary and secondary literature on Islamic law and internet commerce. Islamic legal research on internet commerce reveals that as long as it meets the requirements outlined in fiqh, this behavior is generally acceptable in Islam. This research resulted in the fact that Islamic law allows for buying and selling transactions online. But Islamic law strictly prohibits engaging in fraud, selling prohibited items, and paying interest (usury). Online retailers should refrain from engaging in transactions that do not comply with sharia law. Online transactions can be made simpler and more accessible to technology, but they still need to be modified to comply with the standards and principles of Islamic law.